Iowa RBA, September 4-5, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa RBA update for September 4-5, 1995. Highlights of the update include sightings of a Black-throated Blue Warbler, four Sandhill Cranes, White Ibis, Ruddy Turnstone and two Black-bellied Plovers. Contains numerous reports of Red-breasted Nuthatch sightings. Also included are handwritten notes for the next week's update with sightings of a juvenile Sabine's Gull and a Yellow-crowned Night Heron. Epson - sheet feed/flatbed